Exploring Research Trends in Life Cycle Costing: A Bibliometric Analysis from 2010 to 2025 - Judijanto, Loso; Sumarni, Sumarni (The Es Accounting And Finance, 2026)
This study aims to explore the evolution and research trends of life cycle costing (LCC) through a comprehensive bibliometric analysis of global publications from 2010 to 2025. Using data sourced from the Scopus database and analyzed with VOSviewer, this study examines publication trends, keyword co-occurrence, thematic clusters, and temporal developments in the LCC literature. The results indicate that LCC remains strongly rooted in cost analysis and economic evaluation, particularly within construction, infrastructure, and energy-related sectors. However, the findings also reveal a significant shift toward sustainability-oriented research, as reflected in the growing integration of concepts such as life cycle analysis (LCA), circular economy, environmental assessment, and waste management. Overlay visualization further demonstrates that recent studies increasingly emphasize environmental and interdisciplinary dimensions, while density analysis highlights the dominance of cost-related themes alongside emerging sustainability topics. Despite these advancements, the integration of advanced analytical tools and digital technologies in LCC research remains limited, suggesting opportunities for future development.